Психолого-педагогические основы обучения студентов русскому языку как иностранному средствами компьютерных технологий (SCIENCE and SOCIETY, 2020)
The article identifies and resolves the following tasks: to analyze the state of the use of ICT in the work of Russian language teachers in universities; to identify the pedagogical goals of using ICT tools in the process of teaching the Russian language in a person-centered approach; determine the requirements for the structure, content of educational material and organization of educational activities using ICT tools in Russian language lessons; to develop and experimentally test the effectiveness of pedagogical conditions for the use of ICT tools in improving the quality of teaching the Russian language at a university.